2014
DOI: 10.1007/s00011-014-0747-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5,14-HEDGE, a 20-HETE mimetic, on lipopolysaccharide-induced changes in MyD88/TAK1/IKKβ/IκB-α/NF-κB pathway and circulating miR-150, miR-223, and miR-297 levels in a rat model of septic shock

Abstract: Objectives We have previously demonstrated that a stable synthetic analog of 20-hydroxyeicosatetraenoic acid (20-HETE), N-(20-hydroxyeicosa-5[Z],14[Z]-dienoyl)glycine (5,14-HEDGE), which mimics the effects of endogenously produced 20-HETE, prevents vascular hyporeactivity, hypotension, tachycardia, inflammation, and mortality in a rodent model of septic shock. The present study was performed to determine whether decreased renal and cardiovascular expression and activity of myeloid differentiation factor 88 (My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…In this study, miR-100, miR-297, and miR-758 were chosen as candidate genes after miRNA database prediction indicated that they interact with Col3a1, Agtr1a, and Col1a2, respectively. Previous studies have shown that plasma miR-100 is positively associated with coronary plaque vulnerability [72] can inhibit angiogenesis [73] and is involved in the development and growth of pancreatic cancer [74], while miR-297 is involved in septic shock [75]. In this study, the luciferase assay was used to demonstrate that miR-297 targets AGTR1 and promotes the proliferation of cardiomyocytes by regulating the expression of AGTR1 and CTGF.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, miR-100, miR-297, and miR-758 were chosen as candidate genes after miRNA database prediction indicated that they interact with Col3a1, Agtr1a, and Col1a2, respectively. Previous studies have shown that plasma miR-100 is positively associated with coronary plaque vulnerability [72] can inhibit angiogenesis [73] and is involved in the development and growth of pancreatic cancer [74], while miR-297 is involved in septic shock [75]. In this study, the luciferase assay was used to demonstrate that miR-297 targets AGTR1 and promotes the proliferation of cardiomyocytes by regulating the expression of AGTR1 and CTGF.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of sepsis with lipopolysaccharide (LPS) is associated with activation of MEK1/ERK1/2/IKKbeta/IKB-alpha/NF-KB and MyD88/TAK1/IKKbeta/IKB-alpha/NF-KB pathways that increases the levels of inflammatory cytokines (TNF-alpha and IL-8) (133, 228). These changes, along with the associated hypotension and tachycardia, can be prevented by administration of a stable 20-HETE mimetic, 5, 14-HEDGE.…”
Section: Role Of 20-hete In Vascular Inflammationmentioning
confidence: 99%
“…This has been the subject of several recent and definitive reviews (11, 26, 117121). The role of 20-HETE in ischemic and hemorrhagic stroke (122125), acute renal failure (126, 127), toxemia of pregnancy (128), hepatorenal syndrome (129), vascular restenosis (23), angiogenesis (24), cardiac hypertrophy (130) and ischemia reperfusion (IR) injury (131), as well as shock (132, 133) is less well known and has received little attention in the literature. This review will focus on the emerging pathogenic role of 20-HETE as an important mediator in vascular dysfunction, inflammation in a variety of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Because the disease concept of AIP has become more widely understood among general clinicians, surgical resection of the pancreas for AIP is rarely performed in recent years. Previous studies have shown inflammation-related biological functions of miR-150 [30,31,32]. Lipopolysaccharide increased serum expression level of miR-150 in a rat model of septic shock [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown inflammation-related biological functions of miR-150 [30,31,32]. Lipopolysaccharide increased serum expression level of miR-150 in a rat model of septic shock [30]. miR-150 is a component of a unique signaling network that controls the differentiation of cytotoxic T lymphocytes induced by IL-2 and inflammatory signals [31].…”
Section: Discussionmentioning
confidence: 99%